Exploring the Development of the Sponge City Program (SCP): The Case of Gui'an New District, Southwest China - Qi, Yunfei; Chan, Faith Ka Shun; O'Donnell, Emily C.; Feng, Meili; Sang, Yanfang; Thorne, Colin R.; Griffiths, James; Liu, Lingyun; Liu, Sitong; Zhang, Chunqian; Li, Lei; Thadani, Dimple (Frontiers in Water, 2021)
Rapid urbanization has sharply increased the pressure of urban water issues (e.g., urban flooding and water pollution) in Chinese megacities during the last three decades. Sustainable urban water management approaches, such as Nature Based Solutions (NBS) and Low Impact Developments (LIDs), have successfully delivered long-term benefits to cities in Europe and North America. Similarly, the Chinese Sponge City Program (SCP) initiated in 2013 and experimented in 30 pilot Chinese cities. This paper reviewed the first stage of the SCP from 2015-2020 by using observation, Semi-Structured Interview (SSI) and Focus Group Approach (FGA) in context of Gui’an New Distinct, SW China to investigate the SCP progress and issues: 1. whether it is effectively solving urban water issues; 2. if there are any major challenges and barriers in the SCP practice. The findings of this case study provide potential solutions for improving the SCP and sustainable urban water management and possibly transform to other Sponge Cities.